Comparison of the surface abrasion produced by two different bristle materials – An In vitro pilot study - Richik Chakraborty; Jayaditya Modak; Srishti Agarwal; Balaji Manohar; Manoj Ukamanal; S Bhuvaneshwari (Advances in Human Biology, 2024)
Introduction: Gingival, periodontal diseases and dental caries are the most prevalent diseases of the oral cavity. Plaque is the main cause of these dental diseases. Plaque control is of prime importance for the maintenance of oral and dental health. The toothbrush is used very commonly for plaque control. A variety of toothbrushes are available, which are used for plaque removal. Toothbrushes cause abrasion and are significant in the development of tooth wear. This study aimed to compare the abrasion caused by a commercially available nylon bristle toothbrush to a biobased carbon-based bristle toothbrush. Materials and Methods: Acrylic plates were used to assess the abrasion caused by the nylon bristles and biobased carbon bristles. The surface roughness (Ra) was evaluated on a device, and the values were compared to each other. Results: Brushing with the biobased carbon bristle toothbrush was less abrasive than when nylon bristles were used. The nylon bristles showed a higher Ra value as compared to biobased carbon bristles. Conclusion: The biobased carbon bristles are less abrasive, but studies are required to compare the plaque removal capacity of such biobased carbon bristle toothbrushes.